Board Diversity and Environmental Disclosures: A Study of Indonesian Listed Companies - Rashid, Maryam Agustine Huwaidah; Barokah, Zuni (The Indonesian Journal of Accounting Research, 2024)
This research examines whether the diversity of boards of commissioners and boards of directors affects environmental disclosures. We include all non-financial firms listed on the Indonesian Stock Exchange during 2018-2020 and use the generalized least square (GLS) model. Our findings show that the diversity of age and ethnicity of both the board of commissioners and the board of directors positively influences environmental disclosures. Further, while boards of directors' gender diversity positively affects environmental disclosure, there is no support for the impact of boards of commissioners on the disclosures. Lastly, there is no empirical support for the influence of directors' or commissioners' nationality on the companies' environmental disclosures. The findings highlight the importance of promoting board diversity on both boards of commissioners and directors.